PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS PELANGGAN MOBIL MEREK ‘HONDA’ DI KOTA DENPASAR - Reynaldi, Gede Hadi; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen, 2017)
Honda is one of the largest automotive companies in the world from Japan to produce various types of vehicles. Honda implementing the marketing mix as a strategy to increase sales volume and maintaining customer loyalty. This study aimed to describe the effect on customer loyalty marketing mix Honda brand car in Denpasar. The research sample consisted of 100 people Honda brand car users who live in the city of Denpasar. Data were analyzed using descriptive statistics and inferential statistics such as linear regression. The results showed that the four marketing mix variables significant positive effect on customer loyalty Honda brand car. Four variables, variables most powerful influence is the quality of the product, and the weakest variables endorser credibility. The results showed that when the Honda brand car management wants to maintain or increase customer loyalty, then the marketing mix that is most important to note is the quality of the products, because these variables are the most powerful influence on customer loyalty.
Keywords: product quality, price reasonableness, distribution channels, the credibility of the endorser, customer loyalty